Avaliação da qualidade da água dos rios Jaguarí e Atibaia por meio do índice de qualidade da água - IQA e ensaios toxicológicos - Ramos, Márcio Antônio Gomes [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Aiming at contributing with more detailed information to water managers of water quality of the Jaguari and Atibaia Rivers in the municipality of Paulína / SP, involving a densely populated area and economic importance to the country, this research gathered the data related to the analyses of water, including the Water Quality Index (WQI) and biological assays, from October 2003 to March 2015. During this period, 200 sampling campaigns were performed, approximately at every fortnight, in sampling points at Jaguari River [22°44'48 (S) 47°08'59(W)] and Atibaia River [22°44'22,3(S) 47°07'40,8(W)]. The sampling and analyses were performed according to the methodologies recommended by the National Guide of Sampling and Preservation of Water and Sediment Samples, Aquatic Communities and Liquid Effluents. Nine parameters were analyzed: pH, Dissolved Oxygen, Biochemical Oxygen Demand, Total Nitrogen, Total Phosphorus, Turbidity, Escherichia coli, Total Solids and Temperature. Moreover, acute and chronic toxicities were assessed using Daphnia similis; Ceriodaphnia dubia; Dugesiatigrina and Danio rerio. The sampling campaign consisted of a total of 4195 days, divided in rainy and dry seasons. The rainy season comprised 2265 days, from October to March, constituting 11 periods (P1C; P2C; P3C; P4C; P5C; P6C; P7C; P8C; P9C; P10C and P11C); the dry season comprised 1930 days, from April to September, constituting 10 periods (P1S; P2S; P3S; P4S; P5S; P6S; P7S; P8S; P9S and P10S). For Jaguari River, differences in water quality related to the WQI values were recorded during the 11 periods of rainy season, with 8 presenting regular quality (51-37) and 3 presenting good quality (52-60); in the dry season, from the 10 periods, 2 presented regular quality (48-50) and 8 good quality (53-63), indicating a slight improvement in comparison to rainy season. For Atibaia River, from the 11 periods of rainy season, 1 presented good ...

Visando contribuir com informações mais detalhadas aos gestores hídricos da qualidade das águas dos Rios Jaguari e Atibaia no município de Paulínia / SP, que envolve uma área densamente povoada e de importância econômica para o país, esta pesquisa reuniu os dados relativos às análises de água que envolve o Índice de Qualidade de Água (IQA) e ensaios biológicos no período de outubro de 2003 a março de 2015. Foram efetuadas 200 coletas aproximadamente a cada 15 dias, nos pontos de coleta no Rio Jaguari [22°44'48 (S) 47°08'59(W)] e Rio Atibaia [22°44'22,3(S) 47°07'40,8(W)] no município de Paulínia / SP. As coletas e analises foram realizadas de acordo com as metodologias recomendadas pelo Guia Nacional de Coleta e Preservação de Amostras de Água e Sedimento, Comunidades Aquáticas e Efluentes. Foram efetuadas análises de nove parâmetros: pH, Oxigênio Dissolvido, Demanda Bioquímica de Oxigênio, Nitrogênio total, Fósforo total, Turbidez, Escherichia coli, Sólidos totais e Temperatura. Além destes parâmetros foram executados ensaios biológicos de toxicidade aguda e crônica empregando Daphnia similis; Ceriodaphnia dubia; Dugesia tigrina e Danio rerio. O período de coletas envolveu 4195 dias, sendo dividido em: épocas de chuva, compreendendo os meses de outubro a março, referente há 2265 dias, constituindo de 11 períodos (P1C; P2C; P3C; P4C; P5C; P6C; P7C; P8C; P9C; P10C e P11C); e em épocas de seca incluindo os meses de abril a setembro, referente há 1930 dias, constituindo de 10 períodos (P1S; P2S; P3S; P4S; P5S; P6S; P7S; P8S; P9S e P10S). Verificou-se que ocorreram diferenças na qualidade das águas considerando os valores dos IQA's para o Rio JAGUARI, nos 11 períodos da época de chuva, sendo que 8 indicaram qualidade regular (51 a 37) e 3 boa qualidade (52 a 60); na época de seca, 2 períodos apresentaram qualidade regular (48 a 50) e 8 boa qualidade (53 a 63) indicando...
Keywords: Water - Composition; Agua - Analise; Agua - Composição; Água - Qualidade; Toxicidade - Testes; Paulinia (SP)